Extraction and determination of oryzanol in rice bran of mixed Herbarium UKMB; AZ 6807: MR 185, AZ 6808: MR 211, AZ6809: MR 29 - Azlan, Azrina; Ismail, Maznah; Abdul Hamid, Azizah (Universiti Putra Malaysia Press, 2008)
The level of total lipid and oryzanol content, an important antioxidant compound in locally produced bran was investigated. Total lipid in rice bran was extracted using 3:2 chloroform:methanol mixture yielding 16.4% fat. Oryzanol content was determined without saponification using a reverse-phase HPLC. Four fractions of oryzanol were successfully separated and quantitated. The 4 isomers were cycloartenyl ferulate, 24-methylene cycloartanyl ferulate, campestryl ferulate and mixtures of β–sitosteryl ferulate and cycloartanyl ferulate. The oryzanol content of local mixed varieties ranged from 23.7–43.0 mg g-1. The oryzanol concentration may depend on factors such as plant varieties, processing methods employed, extracting solvent used and ratio of extracting solvent to bran as well as extracting solvent temperatures. This study showed the potential of oryzanol extract from rice bran as a source of antioxidant.